Adab al Arabi Learning at Ma'had Umar bin Al Khattab Putri Sidoarjo During the Covid-19 Pandemic: Pembelajaran Adab al Arabi di Ma'had Umar bin al Khattab Putri Sidoarjo pada masa pandemi Covid-19 - Eka Putri Maghfiroh; Najih Anwar (Academia Open, 2021)
This article aims to determine the learning process of Adab al Arabi at Ma'had Umar Bin al Khattab Putri Sidoarjo. The research approach used by the researcher is a case study study whose data are obtained from a detailed study of a single background, single subject, or a particular event. The results showed that, 1) The online learning method for the Adab Arabi course at Ma'had Umar Bin al-Khattab Putri Sidoarjo during the Covid-19 pandemic was a historical method and in the learning process Ma'had Umar Bin al-Khattab Putri Sidoarjo used several various applications, such as whatsapp, google drive, telegram and youtube. 2) The inhibiting factor in the online learning process for the Adab Arabi course at Ma'had Umar Bin al-Khattab Putri Sidoarjo, namely Mahasisiwi is constrained by signals, cellphone memory is full, internet quota and the lack of enthusiasm of students in participating in online learning for the Adab al Arabi course. 3) Supporting factors for online learning maddah Adab Arabiy, namely, students get time slack in completing assignments, there is no limit on the use of one application in collecting assignments, and students can repeat audio explanations from the ustadzah when they do not understand the material well